POLA KONSUMSI JUNK FOOD DAN STATUS GIZI SISWA SMPN 3 SUKAWATI KABUPATEN GIANYAR - Ni Kadek Desy Roweni; I Putu Suiraoka; I Ketut Kencana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Adolescent nutritional status is very important to support growth and development. Optimal nutritional status will form healthy and productive adolescents. The problem that arises is lack of nutrition and more. Eating habits are a factor in the occurrence of over nutrition in adolescents, especially junk food habits. Research on junk food consumption patterns and nutritional status of students in SMP Negeri 3 Sukawati, Kab. Gianyar, the type of research used is observational research with cross sectional design which is a type of research that emphasizes the time of measurement or observation of data at one time at a time carried out on independent variables and the dependent variable. The population determined was only students in class VII and VIII where class VII and class VIII consisted of 11 classes, namely from class A-K, which totaled 905 students. Samples were taken from a total population of 83 samples, with a sample size of 39 samples. This study aims to see a picture of the relationship of consumption patterns and nutritional status of students at SMP Negeri 3 Sukawati. Linkage of junk food consumption patterns, high consumption types with 25.0% fat status and 12.5% obesity nutritional status. Contribution of junk food consumption with 959.74 kcal of energy fat status, 30.47 grams of protein, 52.67 grams of fat and 61.35 grams of carbohydrate, with energy obesity nutritional status reached 970.28 kcal, 30.18 grams of protein, 61.88 grams of fat and 43.06 grams of carbohydrate. Frequency of junk food consumption is often with obesity nutritional status of 5.0% while frequency of junk food consumption is rarely with very thin nutritional status of 5.0%, obese nutritional status is 25.0% and nutritional status of obesity is 12.5%.Keywords: consumption patterns, junk food, nutritional status